DAMPAK MATERIALISME, PENGENDALIAN DIRI DAN MOTIVASI PADA PERILAKU PENGELOLAAN KEUANGAN KELUARGA - Maria Goreti Hengo; Wehelmina M Ndoen; Paulina Yuritha Amtiran (Journal of Management Small and Medium Enterprises (SMEs), 2021)
This study aimed to analyze the impact of Materialism, Self-Control and Motivation on the Behavior of Family Financial Management in East Penfui Village, Center Kupang District, Kupang Regency. This type of research used survey method, with a qualitative description approach. Data collection techniques used in the form of observation, questionnaires and interviews. The population in this study was the residents of Dusun 1 East Penfui Village with the total of 318 families (KK). The sample of research using purposive sampling and Slovin formula. The sample of research taken as many as 76 respondents. The results of this study indicated that Materialism, Self-Control and Motivation behave well to the Financial Management of families in the Dusun 1 East Penfui Village. Keywords : Materialism, Self-Control, Motivation, Financial Management Behavior